Comparative evaluation of antimicrobial activity of biodentine and MTA against e. faecalis an in vitro study - Jose, Jerin; K, Shoba; Tomy, Nithya; Aman, Shibu (International Journal of Dental Research, 2016)
Background: Surgical endodontic therapy is the prescribed treatment of choice whenever the non-surgical options fail which includes the use of a root end filling material. E. faecalis is the most prevalent organism associated with the treatment failed casesAim: The purpose of the present study was to evaluate and compare the antimicrobial efficacy of Biodentine and MTA as root end filling material and root repair material against E. faecalis.Settings and Design: Comparative invitro study was conducted at Tropical Institute of Ecological Sciences, Kottayam under Mahatma Gandhi University, Kottayam, Kerala.Materials and Methods: The antimicrobial activity was determined using agar diffusion test. Freshly mixed MTA and Biodentine was added to respective wells and incubated. The zone of inhibition of growth was recorded.Statistical analysis: The data analysis was performed using Students ‘t’ testResults: Statistically significant difference was found between Biodentine and MTA in against E. faecalis growth.Conclusions: Biodentine was found to have superior antibacterial activity against E. faecalis than MTA. Hence it can be a better alternative to MTA as root end filling and root repair material.